If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -1x = 10x + -2 Reorder the terms: 20 + -1x = -2 + 10x Solving 20 + -1x = -2 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 20 + -1x + -10x = -2 + 10x + -10x Combine like terms: -1x + -10x = -11x 20 + -11x = -2 + 10x + -10x Combine like terms: 10x + -10x = 0 20 + -11x = -2 + 0 20 + -11x = -2 Add '-20' to each side of the equation. 20 + -20 + -11x = -2 + -20 Combine like terms: 20 + -20 = 0 0 + -11x = -2 + -20 -11x = -2 + -20 Combine like terms: -2 + -20 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 | | -14-4x=13-7x | | 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= | | 6(6v+6)=1+6v | | 12-8x=39-15x | | 2t+11t=104 | | 6x+7=-199-8x | | 14=20-2x | | 30k+10=18k+22 | | 49*7= | | 9d+18=2d+18 | | 2t=-16 | | 18+6m=12m+48 | | 12*6.8= | | 15y+60=30y+120 | | 2.1*6= | | 15y+40=30y+120 | | 18x-30=21x-14 | | 40-8h=4h-8 | | 5X(x+9)=6x+54 | | 24x+5=100 | | 9q-18=3q-36 |